Dielectric Characterization Based On Complementary Split-Ring Resonator - Khee, Yee See; Teoh, H. M. (Emerging Advances in Integrated Technology, 2025)
Material characterization method based on radio frequency and microwave measurements is highly demanded. The dielectric properties is very important for electronic circuit design, food industry, medicine and health care. In this work, a complementary split-ring resonator (CSRR)-based sensor employed in the ground plane is proposed for dielectric measurement. This method enable the determination of both relative permittivity and relative permeability at the same time as well as simple sample preparation process. This project focuses on the design, simulation and the prediction formulae of the CSRR. This CSRR is resonating at 2.477 GHz with a quality factor of 128.91 in unloaded condition. Basically, there are shifting in the resonance frequency and the change of the quality factor when dielectric material is placed at the highest intensity of electric and magnetic fields in separate zones. Four predicted formulas are proposed, which they are depend on the dielectric constant, real permeability, normalized resonance frequency, inverse normalized quality factor, electric loss tangent and magnetic loss tangent of the materials. The prediction formulas are used to measure the permittivity and permeability of FR-4, Polyimide, and self-defined material. Based on the comparison, the percentage error between calculated result and reference data are 10% and 4.1% for electric and magnetic loss tangent respectively. The maximum percentage error in dielectric constant and real permeability are 4.5% and 4.29% respectively. Based on the percentage of error, it is convincing that the prediction formulas are reliable for dielectric measurement. Future work of this project should focus on verification of its actual performance through experimental measurement.